The Micro-Economics Foundations of Islamic Economics: A Study In Social Economics (American Journal of Islam and Society, 1986)
I. Objective of this PaperThe main objective of this paper is to show the relevance of ethical or normativeelements in economic theory. The paper builds on the exchangemechanism of economics as the ethical basis of the social order and showsthat an ethical economic system must be capable of infdtely reproducingthis exchange mechanism in the rational working of the total social systemthrough higher and higher levels of social preferences.In building up this analytical framework of ethical economics, we studythe field of social economics in general and of Islamic economics in particularas a field of social economics. Through this we introduce a reconceptualizationof ethical economics in terms of the fundamental microeconomic buildmgblocks. The premise of the argument therefore is that since the exchangemechanism is the instrument of transmitting ethical preferences, it is themicroeconomic foundation that is capable in the first place of buildmg upthe ethical economic order as a whole. The ethical macroeconomic systemdepends upon aggregations at the microeconomic level.II. IntroductionAs Boulding mentions, economics first started off as a moral science.Adam Smith, who was ”both the Adam and the Smith of systematic economics,”was professor of moral philosophy. Even long after that, economics continuedto be taught as a part of the moral sciences tripos at Cambridge University ...